2016
DOI: 10.1002/2016ja022360
|View full text |Cite
|
Sign up to set email alerts
|

Alfvén wings in the lunar wake: The role of pressure gradients

Abstract: Strongly conducting or magnetized obstacles in a flowing plasma generate structures called Alfvén wings, which mediate momentum transfer between the obstacle and the plasma. Nonconducting obstacles such as airless planetary bodies can generate such structures, which, however, have so far been seen only in sub‐Alfvénic regime. A novel statistical analysis of simultaneous measurements made by two ARTEMIS satellites, one in the solar wind upstream of the Moon and one in the downstream wake, and comparison of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…Moreover, similar compressional effects are also observed in our lower-resolution simulation, as well as in earlier simulations by Poppe et al (2014). The perturbations in the lunar wake arise from a combination of compressional and Alfvénic effects (Zhang et al, 2016). Omidi et al (2019b) show that additional data from the ARTEMIS spacecraft demonstrate that the compressional wake is part of the lunar tail structure and not associated with crustal fields.…”
Section: Lunar Wake Simulationssupporting
confidence: 87%
“…Moreover, similar compressional effects are also observed in our lower-resolution simulation, as well as in earlier simulations by Poppe et al (2014). The perturbations in the lunar wake arise from a combination of compressional and Alfvénic effects (Zhang et al, 2016). Omidi et al (2019b) show that additional data from the ARTEMIS spacecraft demonstrate that the compressional wake is part of the lunar tail structure and not associated with crustal fields.…”
Section: Lunar Wake Simulationssupporting
confidence: 87%
“…As shown in Figure , the intensity of the induced magnetic fields are not high enough to considerably affect the solar wind plasma density and velocity. Previous plasma simulations of the solar wind interaction with unmagnetized atmosphereless bodies, like the Moon and a Saturnian satellite, Rhea, have reported a very similar plasma density structure in the wake of those objects (e.g., Fatemi et al, ; Holmström et al, ; Khurana et al, ; Poppe et al, ; Simon et al, ), which has been confirmed through observations (e.g., Khurana et al, ; Simon et al, ; Zhang et al, , ). The structure of the plasma wake is predominately controlled by the orientation of the IMF with respect to the solar wind plasma flow and the plasma beta (e.g., Ogilvie et al, ; Simon et al, ).…”
Section: Resultssupporting
confidence: 53%
“…In contrast to the single‐fluid MHD model, the multifluid model treats the solar wind protons, water group ions, and the electrons as three coupled fluids. Such a model has recently been applied to the lunar wake in agreement with large‐scale hybrid simulation results modeling solar wind‐Moon interactions with proton gyroradius about 0.6 Moon radii [ Zhang et al , ]. Here the electron fluid is assumed massless, and its density is calculated assuming quasi‐neutrality: n e =Σ s n s Z s , where the subscript s runs through all massive fluids, and Z is the number of proton charges that each particle of the fluid carries.…”
Section: Model Descriptionmentioning
confidence: 99%